The effects of sex and handedness on masturbation laterality and other lateralized motor behaviours. Issue 3 (4th May 2022) - Rodway, Paul; Thoma, Volker; Schepman, Astrid
ABSTRACT: Masturbation is a common human behaviour. Compared to other unimanual behaviours it has unique properties, including increased sexual and emotional arousal, and privacy. Self-reported hand preference for masturbation was examined in 104 left-handed and 103 right-handed women, and 100 left-handed and 99 right-handed men. Handedness (modified Edinburgh Handedness Inventory, EHI), footedness, eyedness, and cheek kissing preferences were also measured. Seventy nine percent used their dominant hand (always/usually) for masturbation, but left-handers (71.5%) were less consistently lateralized to use their dominant hand than right-handers (86.5%). Hand preference for masturbation correlated more strongly with handedness (EHI), than with footedness, eyedness, or cheek preference. There was no difference in masturbation frequency between left- and right-handers, but men masturbated more frequently than women, and more women (75%) than men (33%) masturbated with sex aids. For kissing the preferred cheek of an emotionally close person from the viewer's perspective, left-handers showed a left-cheek preference, and right-handers a weaker right-cheek preference. The results suggest that hemispheric asymmetries in emotion do not influence hand preference for masturbation but may promote a leftward shift in cheek kissing. In all, masturbation is lateralized in a similar way to other manual motor behaviours in left-handed and right-handed men and women.